2022
DOI: 10.23736/s0022-4707.22.13365-7
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic impact on the best performers in athletics and swimming among paralympic and non-disabled athletes

Abstract: BACKGROUND: The COVID 19 pandemic has greatly disrupted high performance sport and international competition. The aim of this study was to quantify the impact of the COVID-19 pandemic on the world's top 10 performances in Athletics and Swimming among nondisabled and Paralympic athletes. METHODS:The results of the 10-best world performers in 66 Olympic events since 1891 and 255 Paralympic events since 2010 were collected. To quantify the performance trend, the slopes of the 4 years moving average were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Contrasting findings were, instead, obtained by Cavaggioni et al (2022), who retrospectively analyzed a case series consisting of four para swimmers. One had cerebral palsy and belonged to the S5 para-swimming functional class, one had a hereditary spastic paraparesis (S6 class), one had a lower limb deficiency (S9 class), and one had lower limb amputation (S8 class).…”
Section: Impact Of Covid-19-induced Confinement On Training and Lifes...mentioning
confidence: 76%
See 4 more Smart Citations
“…Contrasting findings were, instead, obtained by Cavaggioni et al (2022), who retrospectively analyzed a case series consisting of four para swimmers. One had cerebral palsy and belonged to the S5 para-swimming functional class, one had a hereditary spastic paraparesis (S6 class), one had a lower limb deficiency (S9 class), and one had lower limb amputation (S8 class).…”
Section: Impact Of Covid-19-induced Confinement On Training and Lifes...mentioning
confidence: 76%
“…This could explain why Shaw et al (2021) were not able to find any detrimental or disruptive effect of COVID-19 on training among para-athletes, since the outbreak could not influence outdoor activities and training, whereas Martínez-Patiño et al (2021) and Clemente-Suárez et al (2020) reported a positive response from Paralympic athletes to the COVID-19 pandemic. On the contrary, Cavaggioni et al (2022) , and Schipman et al (2022) observed a negative impact of the infectious outbreak.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations